STUDI KOMPARATIF TERHADAP EFEKTIVITAS BERBAGAI TIPE PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN HASIL BELAJAR, KETERLIBATAN AKTIF, DAN KETERAMPILAN SOSIAL PESERTA DIDIK - Mufidah, Zulfin Rachma; Sukartiningsih, Wahyu; Aqida, Elys Nur; Abigael, Nathania Elysia; Nadhiroh, Latifatun; Rahmawati, Lia Ratu; Kurnia, Erma Tri (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
Low learning outcomes, active involvement, and social skills of students are often obstacles in the learning process in elementary schools. One alternative solution that can be applied is the use of cooperative learning models. This study is a comparative study that aims to analyze the effectiveness of various types of cooperative learning models, namely Jigsaw, Think Pair Share, Talking Stick, Scramble, and Paired Storytelling, in improving learning outcomes, active involvement, and social skills of students. The analysis was carried out by comparing the main findings from various literature sources, both in terms of approach, advantages, disadvantages, and their impact on student learning outcomes. The results of the study show that the five types of models have their respective advantages: Jigsaw is effective in encouraging in-depth understanding of the material, Think-Pair-Share strengthens active participation, Paired Storytelling improves interpersonal communication, Scramble encourages speed of thinking and teamwork, and Talking Stick strengthens courage and social skills. This study recommends the use of cooperative learning models in a variety of ways according to learning objectives. ABSTRAKRendahnya hasil belajar, keterlibatan aktif, dan keterampilan sosial peserta didik sering kali menjadi hambatan dalam proses pembelajaran di sekolah dasar. Salah satu alternatif solusi yang dapat diterapkan adalah penggunaan model pembelajaran kooperatif. Penelitian ini merupakan studi komparatif yang bertujuan untuk menganalisis efektivitas berbagai tipe model pembelajaran kooperatif, yaitu Jigsaw, Think Pair Share, Talking Stick, Scrambel, dan Paired Storytelling, dalam meningkatkan hasil belajar, keterlibatan aktif, dan keterampilan sosial peserta didik. Analisis dilakukan dengan membandingkan temuan-temuan utama dari berbagai sumber literatur, baik dari segi pendekatan, kelebihan, kekurangan, maupun dampaknya terhadap capaian belajar peserta didik. Hasil kajian menunjukkan bahwa kelima tipe model memiliki keunggulan masing-masing : Jigsaw efektif dalam mendorong pemahaman materi secara mendalam, Think-Pair-Share memperkuat partisipasi aktif, Paired Storytelling meningkatkan komunikasi interpersonal, Scramble mendorong kecepatan berpikir dan kerja tim, serta Talking Stick memperkuat keberanian dan keterampilan sosial. Kajian ini merekomendasikan pemanfaatan model pembelajaran kooperatif secara variatif sesuai dengan tujuan pembelajaran.